The ophthalmology examinations review - Wong, Tien Yin; Lim, Laurence; Sng, Chelvin (New Jersey : World Scientific, 2011)
Many treatments and diagnostic procedures in ophthalmology have been refined over the years. This book provides a review of the specialist ophthalmology examinations for final year ophthalmology residents and trainees. It deals primarily with key facts and topics that are important from the examination perspective
1. Cataract and cataract surgery -- 2. Glaucoma and glaucoma surgery -- 3. Corneal and external eye diseases -- 4. Surgical retina -- 5. Medical retina -- 5. Neuroophthalmology -- 6. Oculoplastic and orbital diseases -- 7. Uveitis, systemic diseases, and tumors -- 8. Squints and pediatric eye diseases -- 9. Miscellaneous examination problems
Includes bibliographical references and index
Keywords: Ophthalmology -- Examinations, questions, etc; Ophthalmology -- Outlines, syllabi, etc; Eye -- Diseases -- Examination Questions; Ophthalmologic Surgical Procedures -- Examination Questions